Constitutive models of pavement asphaltic layers based on mixture compositions - Zbiciak, Artur; Brzeziński, Karol; Michalczyk, Rafał (Journal of Civil Engineering and Management, 2017)
The design of flexible and semi-rigid pavements by applying mechanistic-empirical methods involves the determination of the stress and strain states in accordance with the assumptions of continuum mechanics. Advanced computational models should take into account the rheological properties of asphalt layers. Precise identification of visco-elastic parameters of asphalt aggregate mixtures requires a lot of expensive laboratory experiments. The objective of this paper is to propose a new method allowing the identification of visco-elastic constitutive parameters based only on the mixture composition. The effectiveness of the proposed approach is exemplified in the paper by numerical calculations. Two linear rheological models were analyzed: the classical Burgers model and the Huet-Sayegh model described by fractional derivatives. Constitutive parameters of both models were obtained from the appropriate optimization algorithms and numerical techniques for determining inverse Laplace transforms. First published online: 13 Jun 2016